2019
DOI: 10.1136/ijgc-2018-000095
|View full text |Cite
|
Sign up to set email alerts
|

A new marker based on risk stratification of human papillomavirus DNA and tumor size to predict survival of locally advanced cervical cancer

Abstract: ObjectiveTo assess the prognostic value of human papillomavirus (HPV) viral load in locally advanced cervical carcinoma treated with radical concurrent chemoradiotherapy.MethodsFrom January 2012 to October 2013, a total of 246 locally advanced cervical carcinoma patients were included in this retrospective study. HPV DNA status was tested by Hybrid Capture 2 assay. Tumor size was measured on T2WI. All the patients in the study received concurrent cisplatin-based chemoradiotherapy with intensity-modulated radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Determining the predictive value of the HPV viral load was the objective of several studies. In locally advanced cervical cancer, a low HPV viral load was associated with an impaired distant metastasis free (DMFS) and overall survival (OS), while the combined analysis HPV viral load and tumor size were superior for predicting OS [70]. These findings are consistent with the findings by Kim et al, who reported worse disease-free survival (DFS) in 169 women with low HPV viral load treated with CRT [71].…”
Section: Prognostic Impact Of Hpv Viral Loadsupporting
confidence: 83%
“…Determining the predictive value of the HPV viral load was the objective of several studies. In locally advanced cervical cancer, a low HPV viral load was associated with an impaired distant metastasis free (DMFS) and overall survival (OS), while the combined analysis HPV viral load and tumor size were superior for predicting OS [70]. These findings are consistent with the findings by Kim et al, who reported worse disease-free survival (DFS) in 169 women with low HPV viral load treated with CRT [71].…”
Section: Prognostic Impact Of Hpv Viral Loadsupporting
confidence: 83%
“…It also has been reported that residual HPV DNA is clinically useful as a new marker to predict local recurrence after conization for cervical intraepithelial neoplasia14–18 and after RT for invasive cervical carcinoma 19–28. In the study conducted by the University of the Ryukyus in Japan, local recurrence rate was significantly higher in patients with persistent HPV than in patients cleared for HPV who were treated with RT (34% vs 7.1%).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to tumor volume, performance status, treatment received, and prognostic factors for locally advanced cervical cancers, such as age, race, stage, histological type, grade, lymph node enlargement, and location, are associated with poor outcomes 4 . Several studies have focused on the prognostic factors for patients receiving CCRT in locally advanced cervical cancer, and it has been reported that larger tumor size and high-risk HPV were correlated with prognosis 13 , 14 . However, most studies have targeted operable cases.…”
Section: Introductionmentioning
confidence: 99%